Automatización del proceso de elaboración de queso fresco semiblando entero de la empresa El Campesino - Ramos Soria, Ricardo Bolívar (2018)
The company of lactic “El Campesino” has come developing during his twenty years of entrepreneurial life the production of the semi-soft cottage cheese of manual form, reason for which, and you have experienced the development of the automatization of an one belonging to his kettles of production with the enthusiasm of rendering an improvement in the quality of your product and in concordance with the present-day modernization. It has been been able to manufacture an equipment in accord with the surroundings of the plant by means of the electric and electronic teams' execution of mechanical works of adaptation and user-friendly for the laborer, as well as with a PLC's application the stages of production come true without the need of a permanent laborer, permitting a substantial improvement in production and in the quality of the product due to the standardization of the quality of the product. An invention dials the implementation of the automatization at the company to local level of the form of production allowing to be pioneer in the improvement of the productive processes at the companies of production of semi-soft cottage cheese. You obtained a decrease in the time of the process as a result of automatization, for there an improvement in the cost-reducing company profitability owed to than the laborer once the supervision was destined of temperature and permanent dairy agitation can develop others own activities of the process of elaboration of the semi-soft cottage cheese.